Toy story 2 = Oyuncak hikayesi 2 - Lasseter, John; Walt Disney Pictures (Hollywood, LA : Walt Disney, 1999)
When Woody is stolen by a toy collector, Buzz and his friends vow to rescue him, but Woody finds the idea of immortality in a museum tempting.
Region 2.
Voices : Tom Hanks, Tim Allen,Joan Cusack.
K-3.
Languages : Turkish, English, German.
Subtitles : Turkish, English, English for the hearing impaired, German.
Keywords: Movie -- animated films; Toys -- Movie